Comparison of effectiveness between two different doses of intravenous dexmedetomidine as adjuvant to subarachnoid block for sub umbilical surgeries - Sahoo, Ayaskant; Seelan, Padmalatha; Dasari, Gurucharan; Penmatsa, Swathi (Journal of Medical Science, 2023)
Background. Spinal anesthesia was a commonly used technique in anesthetic practice for lower abdominal and lower limb surgeries. To prolong the duration of bupivacaine spinal anesthesia adjuvants like α2 agonists and opioids have been used intrathecally. Clonidine and dexmedetomidine have also been found to prolong the duration of spinal anesthesia when given intravenous. Dexmedetomidine was more suitable adjuvant to spinal anesthesia compared to clonidine as it has more sedative and analgesic effects due to more selective α2A receptor agonist activity. Dexmedetomidine has been shown to prolong the duration of analgesia of spinal anaesthesia in various studies. Here we compare the two doses of Dexmedetomidine in prolonging the duration of analgesia.Material and methods. 60 American Society of Anaesthesiologists(ASA) physical status I/II patients scheduled for elective lower abdominal and lower limb surgeries under spinal anesthesia were randomized into two groups of 30 each. Immediately after subarachnoid block with 3.5ml of 0.5% hyperbaric bupivacaine, Group A patients received a loading dose of 0.5µg/kg of dexmedetomidine intravenously in 100ml NS over 10 mins whereas Group B received 1.0µg/kg of dexmedetomidine intravenously in 100ml NS over 10 mins.Results. Time for rescue analgesic were higher in Group B compared to Group A which was statistically significant but clinically the extra duration was insignificant. Time for two segment regression and duration of motor blockade was significantly prolonged in Group B. Requirement of Mephentermine was comparable in both the groups. There was no excessive sedation in both the groups.Conclusion. Dexmedetomidine administered as isolated loading dose of 0.5 µg/kg IV immediately after spinal anaesthesia was clinically equi-efficacious in prolonging the duration of analgesia of spinal anaesthesia compared to a larger dose of 1.0 µg/kg. The side effect profile, hemodynamic stability, sedation levels, need for vasopressors and atropine were comparable in both groups.